TOEFL Essentials: Effective Training to Master Grammar and Structure for Students - Sri Astuti Nasir; Rostina; Iswardhani, Indri; Windarsari, Wiwin Riski; Sandira, Nur Fadilah Ayu (Abdi Cendekia : Jurnal Pengabdian Masyarakat, 2025)
The TOEFL preparation training program conducted for students aimed to enhance their proficiency in key areas of TOEFL, with a particular focus on grammar and structure. The training utilized a pretest-posttest design, where a pretest was administered to assess students' initial skills, followed by targeted lessons on basic grammar concepts, sentence structure, the use of "to be," and prepositions. The program concluded with a posttest to evaluate improvements. Results showed a significant increase in students' average scores, from 61 on the pretest to 82 on the posttest, demonstrating the effectiveness of the training. The use of interactive exercises, practical applications, and real-time feedback contributed to the overall success of the program. This community service initiative not only improved students' TOEFL performance but also provided them with essential tools for academic and professional success.